Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Sure! Let's work through the problem step-by-step using synthetic division for each rational expression:
### Part (a)
[tex]\[ \frac{x^2 - 17x - 33}{x + 2} \][/tex]
Here, we are dividing [tex]\(x^2 - 17x - 33\)[/tex] by [tex]\(x + 2\)[/tex].
1. Set [tex]\(x + 2 = 0\)[/tex] which gives [tex]\(x = -2\)[/tex], the value we will use for synthetic division.
2. Coefficients of the polynomial [tex]\(x^2 - 17x - 33\)[/tex] are [tex]\( [1, -17, -33] \)[/tex].
Using synthetic division:
- Write down the coefficients: [tex]\(1, -17, -33\)[/tex].
- Bring down the first coefficient: [tex]\(1\)[/tex].
- Multiply by [tex]\(-2\)[/tex] (value of [tex]\(x\)[/tex]): [tex]\(1 \cdot (-2) = -2\)[/tex].
- Write the result under the next coefficient and add: [tex]\(-17 + (-2) = -19\)[/tex].
- Multiply by [tex]\(-2\)[/tex] again: [tex]\(-19 \cdot (-2) = 38\)[/tex].
- Write the result under the next coefficient and add: [tex]\(-33 + 38 = 5\)[/tex].
The quotient is [tex]\(x - 19\)[/tex] and the remainder is [tex]\(5\)[/tex]. So:
[tex]\[ \frac{x^2 - 17x - 33}{x + 2} = (x - 19) + \frac{5}{x + 2} \][/tex]
### Part (b)
[tex]\[ \frac{2x^2 - 9x + 19}{x - 6} \][/tex]
Here, we are dividing [tex]\(2x^2 - 9x + 19\)[/tex] by [tex]\(x - 6\)[/tex].
1. Set [tex]\(x - 6 = 0\)[/tex] which gives [tex]\(x = 6\)[/tex].
2. Coefficients of the polynomial [tex]\(2x^2 - 9x + 19\)[/tex] are [tex]\([2, -9, 19]\)[/tex].
Using synthetic division:
- Write down the coefficients: [tex]\(2, -9, 19\)[/tex].
- Bring down the first coefficient: [tex]\(2\)[/tex].
- Multiply by [tex]\(6\)[/tex] (value of [tex]\(x\)[/tex]): [tex]\(2 \cdot 6 = 12\)[/tex].
- Write the result under the next coefficient and add: [tex]\(-9 + 12 = 3\)[/tex].
- Multiply by [tex]\(6\)[/tex] again: [tex]\(3 \cdot 6 = 18\)[/tex].
- Write the result under the next coefficient and add: [tex]\(19 + 18 = 37\)[/tex].
The quotient is [tex]\(2x + 3\)[/tex] and the remainder is [tex]\(37\)[/tex]. So:
[tex]\[ \frac{2x^2 - 9x + 19}{x - 6} = (2x + 3) + \frac{37}{x - 6} \][/tex]
### Part (c)
[tex]\[ \frac{x^3 - 2x^2 + 7x - 25}{x - 3} \][/tex]
Here, we are dividing [tex]\(x^3 - 2x^2 + 7x - 25\)[/tex] by [tex]\(x - 3\)[/tex].
1. Set [tex]\(x - 3 = 0\)[/tex] which gives [tex]\(x = 3\)[/tex].
2. Coefficients of the polynomial [tex]\(x^3 - 2x^2 + 7x - 25\)[/tex] are [tex]\([1, -2, 7, -25]\)[/tex].
Using synthetic division:
- Write down the coefficients: [tex]\(1, -2, 7, -25\)[/tex].
- Bring down the first coefficient: [tex]\(1\)[/tex].
- Multiply by [tex]\(3\)[/tex] (value of [tex]\(x\)[/tex]): [tex]\(1 \cdot 3 = 3\)[/tex].
- Write the result under the next coefficient and add: [tex]\(-2 + 3 = 1\)[/tex].
- Multiply by [tex]\(3\)[/tex] again: [tex]\(1 \cdot 3 = 3\)[/tex].
- Write the result under the next coefficient and add: [tex]\(7 + 3 = 10\)[/tex].
- Multiply by [tex]\(3\)[/tex] again: [tex]\(10 \cdot 3 = 30\)[/tex].
- Write the result under the next coefficient and add: [tex]\(-25 + 30 = 5\)[/tex].
The quotient is [tex]\(x^2 + x + 10\)[/tex] and the remainder is [tex]\(5\)[/tex]. So:
[tex]\[ \frac{x^3 - 2x^2 + 7x - 25}{x - 3} = (x^2 + x + 10) + \frac{5}{x - 3} \][/tex]
### Part (d)
[tex]\[ \frac{2x^3 + 13x^2 + 20x - 12}{x + 4} \][/tex]
Here, we are dividing [tex]\(2x^3 + 13x^2 + 20x - 12\)[/tex] by [tex]\(x + 4\)[/tex].
1. Set [tex]\(x + 4 = 0\)[/tex] which gives [tex]\(x = -4\)[/tex].
2. Coefficients of the polynomial [tex]\(2x^3 + 13x^2 + 20x - 12\)[/tex] are [tex]\([2, 13, 20, -12]\)[/tex].
Using synthetic division:
- Write down the coefficients: [tex]\(2, 13, 20, -12\)[/tex].
- Bring down the first coefficient: [tex]\(2\)[/tex].
- Multiply by [tex]\(-4\)[/tex] (value of [tex]\(x\)[/tex]): [tex]\(2 \cdot (-4) = -8\)[/tex].
- Write the result under the next coefficient and add: [tex]\(13 + (-8) = 5\)[/tex].
- Multiply by [tex]\(-4\)[/tex] again: [tex]\(5 \cdot (-4) = -20\)[/tex].
- Write the result under the next coefficient and add: [tex]\(20 + (-20) = 0\)[/tex].
- Multiply by [tex]\(-4\)[/tex] again: [tex]\(0 \cdot (-4) = 0\)[/tex].
- Write the result under the next coefficient and add: [tex]\(-12 + 0 = -12\)[/tex].
The quotient is [tex]\(2x^2 + 5x\)[/tex] and the remainder is [tex]\(-12\)[/tex]. So:
[tex]\[ \frac{2x^3 + 13x^2 + 20x - 12}{x + 4} = (2x^2 + 5x) + \frac{-12}{x + 4} \][/tex]
In summary:
[tex]\[ (a) \frac{x^2 - 17x - 33}{x + 2} = (x - 19) + \frac{5}{x + 2} \][/tex]
[tex]\[ (b) \frac{2x^2 - 9x + 19}{x - 6} = (2x + 3) + \frac{37}{x - 6} \][/tex]
[tex]\[ (c) \frac{x^3 - 2x^2 + 7x - 25}{x - 3} = (x^2 + x + 10) + \frac{5}{x - 3} \][/tex]
[tex]\[ (d) \frac{2x^3 + 13x^2 + 20x - 12}{x + 4} = (2x^2 + 5x) + \frac{-12}{x + 4} \][/tex]
### Part (a)
[tex]\[ \frac{x^2 - 17x - 33}{x + 2} \][/tex]
Here, we are dividing [tex]\(x^2 - 17x - 33\)[/tex] by [tex]\(x + 2\)[/tex].
1. Set [tex]\(x + 2 = 0\)[/tex] which gives [tex]\(x = -2\)[/tex], the value we will use for synthetic division.
2. Coefficients of the polynomial [tex]\(x^2 - 17x - 33\)[/tex] are [tex]\( [1, -17, -33] \)[/tex].
Using synthetic division:
- Write down the coefficients: [tex]\(1, -17, -33\)[/tex].
- Bring down the first coefficient: [tex]\(1\)[/tex].
- Multiply by [tex]\(-2\)[/tex] (value of [tex]\(x\)[/tex]): [tex]\(1 \cdot (-2) = -2\)[/tex].
- Write the result under the next coefficient and add: [tex]\(-17 + (-2) = -19\)[/tex].
- Multiply by [tex]\(-2\)[/tex] again: [tex]\(-19 \cdot (-2) = 38\)[/tex].
- Write the result under the next coefficient and add: [tex]\(-33 + 38 = 5\)[/tex].
The quotient is [tex]\(x - 19\)[/tex] and the remainder is [tex]\(5\)[/tex]. So:
[tex]\[ \frac{x^2 - 17x - 33}{x + 2} = (x - 19) + \frac{5}{x + 2} \][/tex]
### Part (b)
[tex]\[ \frac{2x^2 - 9x + 19}{x - 6} \][/tex]
Here, we are dividing [tex]\(2x^2 - 9x + 19\)[/tex] by [tex]\(x - 6\)[/tex].
1. Set [tex]\(x - 6 = 0\)[/tex] which gives [tex]\(x = 6\)[/tex].
2. Coefficients of the polynomial [tex]\(2x^2 - 9x + 19\)[/tex] are [tex]\([2, -9, 19]\)[/tex].
Using synthetic division:
- Write down the coefficients: [tex]\(2, -9, 19\)[/tex].
- Bring down the first coefficient: [tex]\(2\)[/tex].
- Multiply by [tex]\(6\)[/tex] (value of [tex]\(x\)[/tex]): [tex]\(2 \cdot 6 = 12\)[/tex].
- Write the result under the next coefficient and add: [tex]\(-9 + 12 = 3\)[/tex].
- Multiply by [tex]\(6\)[/tex] again: [tex]\(3 \cdot 6 = 18\)[/tex].
- Write the result under the next coefficient and add: [tex]\(19 + 18 = 37\)[/tex].
The quotient is [tex]\(2x + 3\)[/tex] and the remainder is [tex]\(37\)[/tex]. So:
[tex]\[ \frac{2x^2 - 9x + 19}{x - 6} = (2x + 3) + \frac{37}{x - 6} \][/tex]
### Part (c)
[tex]\[ \frac{x^3 - 2x^2 + 7x - 25}{x - 3} \][/tex]
Here, we are dividing [tex]\(x^3 - 2x^2 + 7x - 25\)[/tex] by [tex]\(x - 3\)[/tex].
1. Set [tex]\(x - 3 = 0\)[/tex] which gives [tex]\(x = 3\)[/tex].
2. Coefficients of the polynomial [tex]\(x^3 - 2x^2 + 7x - 25\)[/tex] are [tex]\([1, -2, 7, -25]\)[/tex].
Using synthetic division:
- Write down the coefficients: [tex]\(1, -2, 7, -25\)[/tex].
- Bring down the first coefficient: [tex]\(1\)[/tex].
- Multiply by [tex]\(3\)[/tex] (value of [tex]\(x\)[/tex]): [tex]\(1 \cdot 3 = 3\)[/tex].
- Write the result under the next coefficient and add: [tex]\(-2 + 3 = 1\)[/tex].
- Multiply by [tex]\(3\)[/tex] again: [tex]\(1 \cdot 3 = 3\)[/tex].
- Write the result under the next coefficient and add: [tex]\(7 + 3 = 10\)[/tex].
- Multiply by [tex]\(3\)[/tex] again: [tex]\(10 \cdot 3 = 30\)[/tex].
- Write the result under the next coefficient and add: [tex]\(-25 + 30 = 5\)[/tex].
The quotient is [tex]\(x^2 + x + 10\)[/tex] and the remainder is [tex]\(5\)[/tex]. So:
[tex]\[ \frac{x^3 - 2x^2 + 7x - 25}{x - 3} = (x^2 + x + 10) + \frac{5}{x - 3} \][/tex]
### Part (d)
[tex]\[ \frac{2x^3 + 13x^2 + 20x - 12}{x + 4} \][/tex]
Here, we are dividing [tex]\(2x^3 + 13x^2 + 20x - 12\)[/tex] by [tex]\(x + 4\)[/tex].
1. Set [tex]\(x + 4 = 0\)[/tex] which gives [tex]\(x = -4\)[/tex].
2. Coefficients of the polynomial [tex]\(2x^3 + 13x^2 + 20x - 12\)[/tex] are [tex]\([2, 13, 20, -12]\)[/tex].
Using synthetic division:
- Write down the coefficients: [tex]\(2, 13, 20, -12\)[/tex].
- Bring down the first coefficient: [tex]\(2\)[/tex].
- Multiply by [tex]\(-4\)[/tex] (value of [tex]\(x\)[/tex]): [tex]\(2 \cdot (-4) = -8\)[/tex].
- Write the result under the next coefficient and add: [tex]\(13 + (-8) = 5\)[/tex].
- Multiply by [tex]\(-4\)[/tex] again: [tex]\(5 \cdot (-4) = -20\)[/tex].
- Write the result under the next coefficient and add: [tex]\(20 + (-20) = 0\)[/tex].
- Multiply by [tex]\(-4\)[/tex] again: [tex]\(0 \cdot (-4) = 0\)[/tex].
- Write the result under the next coefficient and add: [tex]\(-12 + 0 = -12\)[/tex].
The quotient is [tex]\(2x^2 + 5x\)[/tex] and the remainder is [tex]\(-12\)[/tex]. So:
[tex]\[ \frac{2x^3 + 13x^2 + 20x - 12}{x + 4} = (2x^2 + 5x) + \frac{-12}{x + 4} \][/tex]
In summary:
[tex]\[ (a) \frac{x^2 - 17x - 33}{x + 2} = (x - 19) + \frac{5}{x + 2} \][/tex]
[tex]\[ (b) \frac{2x^2 - 9x + 19}{x - 6} = (2x + 3) + \frac{37}{x - 6} \][/tex]
[tex]\[ (c) \frac{x^3 - 2x^2 + 7x - 25}{x - 3} = (x^2 + x + 10) + \frac{5}{x - 3} \][/tex]
[tex]\[ (d) \frac{2x^3 + 13x^2 + 20x - 12}{x + 4} = (2x^2 + 5x) + \frac{-12}{x + 4} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.